Pengaruh Unsur Hara Untuk Kehidupan Biota Pada Perairan Estuari - Mendrofa, Elrica April Yanti (CV. SINAR HOWUHOWU, 2025)
Estuary waters are transitional ecosystems between marine and terrestrial environments that are highly productive but vulnerable to environmental degradation. productive but vulnerable to environmental damage, especially due to nutrient pollution from human activities. Literature studies in the last five years the last five years have shown that key nutrient elements such as nitrate, phosphate and ammonium play an important role in estuary ecosystem dynamics. High concentrations of nitrate and phosphate concentrations are associated with an increase in phytoplankton, but can also lead to potential eutrophication. can lead to potential eutrophication, Changes in currents due to nutrient inputs affect the composition of the plankton community in the estuary, river flows carry high nutrient loads from the land which accelerates the eutrophication process as well as changes in the trophic status of the waters. changes in the trophic status of the waters. This article aims to assess the influence of nutrients on estuary waters based on a literature review, and provide recommendations for sustainable ecosystem-based management.